2016
DOI: 10.1007/s11274-016-2115-3
|View full text |Cite
|
Sign up to set email alerts
|

Selection of strains for shiitake production in axenic substrate

Abstract: Shiitake mushroom consumption is increasing in Brazil. In addition to the implementation of new production methods, it is also important to increase productivity, quality and reduce production costs. In this study, six commercial Lentinula edodes strains were characterized for genetic diversity (rep-PCR analysis) and mushroom production (yield, number and weight of individual mushrooms) using different substrates and cultural conditions. All strains showed genetic differences by repetitive element palindromic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…Philippoussis et al (2003) tested three formulations of substrates containing increasing concentrations of hemicellulose for L. edodes cultivation and found faster growth and early fruiting in the two substrates with highest content of hemicellulose. Zied et al (2016) reported higher mushroom yield when the sawdust-based substrate was supplemented with diverse kinds of bran or meal. Those supplements likely enriched the substrate with hemicellulose and soluble sugars, besides nitrogen, vitamins, amino acids, etc.…”
Section: Lignin Cellulose and Hemicellulosementioning
confidence: 99%
See 4 more Smart Citations
“…Philippoussis et al (2003) tested three formulations of substrates containing increasing concentrations of hemicellulose for L. edodes cultivation and found faster growth and early fruiting in the two substrates with highest content of hemicellulose. Zied et al (2016) reported higher mushroom yield when the sawdust-based substrate was supplemented with diverse kinds of bran or meal. Those supplements likely enriched the substrate with hemicellulose and soluble sugars, besides nitrogen, vitamins, amino acids, etc.…”
Section: Lignin Cellulose and Hemicellulosementioning
confidence: 99%
“…Six strains of Lentinula edodes (UFLA-LE1, UFLA-LE2, UFLA-LE3, UFLA-LE4, UFLA-LE5 and UFLA-LE6) as described by Zied et al (2016) were utilized. The stock cultures were maintained on malt agar medium (15.0 g L -1 of glucose; 15.0 g L -1 of malt extract; 15.0 g L -1 of agar) and incubated at 25 °C.…”
Section: Fungus and Culture Conditionsmentioning
confidence: 99%
See 3 more Smart Citations